2017
DOI: 10.1038/ncomms15957
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli FtsA forms lipid-bound minirings that antagonize lateral interactions between FtsZ protofilaments

Abstract: Most bacteria divide using a protein machine called the divisome that spans the cytoplasmic membrane. Key divisome proteins on the membrane’s cytoplasmic side include tubulin-like FtsZ, which forms GTP-dependent protofilaments, and actin-like FtsA, which tethers FtsZ to the membrane. Here we present genetic evidence that in Escherichia coli, FtsA antagonizes FtsZ protofilament bundling in vivo. We then show that purified FtsA does not form straight polymers on lipid monolayers as expected, but instead assemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
117
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(136 citation statements)
references
References 80 publications
14
117
3
Order By: Relevance
“…A–B). In addition, the presence or absence of ATP in the reactions did not have reproducible effects on the structures formed, as was observed previously (Szwedziak et al , ; Krupka et al , ). We then asked whether adding higher concentrations of proteins might drive their oligomerization into different structures, including more minirings.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…A–B). In addition, the presence or absence of ATP in the reactions did not have reproducible effects on the structures formed, as was observed previously (Szwedziak et al , ; Krupka et al , ). We then asked whether adding higher concentrations of proteins might drive their oligomerization into different structures, including more minirings.…”
Section: Resultssupporting
confidence: 80%
“…As FtsA* forms short arcs when bound to the lipid monolayer instead of minirings, we showed that this structural change removes the constraints on miniring‐bound FtsZ protofilaments to laterally interact, allowing FtsZ protofilaments to bundle (Krupka et al , ). Considering that three of the FtsA*‐like mutants also bypass ZipA and form alternative structures on lipid monolayers, we predicted that the mutant proteins would also allow FtsZ filaments to bundle.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations